Program Gizi atau Bencana Gizi ? Tinjauan Kritis atas Keracunan Massal Siswa pada Program Makan Bergizi Gratis di Indonesia - Siti Morizana Hardayanti; Siti Fatimah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2026)
The free nutritious Meal Program (MBG), initiated by the Indonesian government in 2025, was originally conceived with the noble aspiration of improving nutritional status among school-aged children across the country. However, field realities have revealed a picture starkly divergent from the program’s foundational objectives. Throughout 2025 and into early 2026, no fewer than 33,626 students across 31 provinces were reported to have suffered food poisoning following the consumption of meals distributed under this initiative. This phenomenon raises fundamental questions regarding the adequacy of food safety governance, within a program funded by a national budget amounting to hundreds of trillions of rupiah. This study aims to critically examine the contributing factors underlying mass food poisoning incidents among students in the MBG program, with particular emphasis on the deficiencies in sanitation and hygiene oversight within the Nutrition Fulfillment Service Units (SPPG), the absence of operational certification, and non compliance with food distribution chain standards. A qualitative research approach was employed, utilizing case study methodology and in-depth interviews conducted with key stakeholders, including SPPG kitchen managers, community health center personnel, education departement officials, and parents of affected students. Data analysis was carried out through source triangulation techniques to ensure the validity and credibility of findings. The results indicate that repeated mass poisonings are not isolated incidents, but rather reflect systemic failures in the planning, oversight, and accountability of the MBG program as a whole. The absence of standard operating procedures, weak coordination between institutions, and minimal human resource capacity at the SPPG level are the root causes of the problem, which have so far escaped policy attention. This study recommends comprehensive reform of the MBG program’s food safety oversight mechanisms, including the implementation of a system, strengthening the role of regional health departements as independent supervisors, and establishing a transparent and accountable incident reporting mechanism.